Pulmonary non-tuberculous mycobacteria and Mycobacterium tuberculosis complex co-infection: A pragmatic approach to its diagnosis and management in South Africa - C Opperman; S Singh; Y Ghebrekristos; R Warren; W Goosen (South African Medical Journal)
-